Profile of students’ scientific literacy on particle dynamics - Mahtari, S; Wati, M; Rizky, S; Dewantara, D; Prahani, B K (Journal of physics. Conference series, 2021)
This study measures students’ ability to complete scientific literacy instruments on particle dynamics material analyzed using the Rasch model. This study uses a quantitative descriptive research design with a survey method. The research subjects were 29 students of class XI IPA 2 at State Senior High School 6 Banjarmasin. The data collection technique was carried out using a scientific literacy test on particle dynamics material in the form of reasoned multiple choice questions as many as ten questions. The research data were analyzed using the Rasch model with the Winstep program. The results showed that the MNSQ outfit was 0.94, Outfit ZSTD was 0.05, person reliability was 0.58 in the weak category, Cronbach’s alpha reliability was 0.92, the separation value was 1.17 with two groups. The students’ scientific literacy ability is quite good but still needs to be improved and retrained.